THE DEPENDENCE OF TRANSLOCATOR PROTEIN TSPO LEVEL AND CYTOCHROME P450SCC FROM HISTOTYPE OF TUMOR IN PATIENTS WITH RENAL CELL CARCINOMA - R. A. Zukov; T. G. Ruksha; Yu. A. Dykhno; E. V. Semenov; N. V. Boyakova (Сибирский онкологический журнал)
The features of expression of translocator protein (TSPO) and cytochrome P450scc (CYP 450scc) in patients with renal cell carcinoma (RCC) were described in the article. The dependence of level expression of TSPO from stage and histological subtypes of renal cell carcinoma were established. The changing of expression level of CYP 450scc in tumor cells indicates a change of severity of steroidogenesis in different histological subtypes of RCC. These findings were important for interpretation the pathogenesis of RCC and also they could have prognostic value